Analisis Keterlaksanaan Komponen Program Kampus Mengajar di SD Inpres Kampus Unhas - Gusti Handayana; Supriadi Supriadi; Erwin Nurdiansyah (STKIP Andi Matappa Pangkep, 2023)
This research aims to analyze the implementation of campus teaching program components at SD Inpres, Unhas Campus. The type of research used is a qualitative method because, in its actions, the researcher identifies the implementation of campus teaching program components, namely literacy, numeracy, and technology adaptation. The location of this research is SD Inpres, Unhas Campus. Data collection techniques in research include observation, interviews, and documentation. Based on the results of this research, several cases were found of students whose literacy and numeracy skills were still very poor; therefore, the author and the team held a class to help and guide these students until several meetings showed quite satisfactory progress in addition to their abilities. The adaptation of technology at the school is much more developed than before. The author and team helped the teaching staff at the school adapt more closely to technology. In this campus teaching program, students are appointed to take part in the program and have responsibilities in helping the school, such as assisting in teaching, adapting technology, and assisting school administration.